kit0058
kit0058 kit0058
  • 02-03-2017
  • Mathematics
contestada

solve by elimination

solve by elimination class=

Respuesta :

roseberline
roseberline roseberline
  • 02-03-2017
2x - 2y = -4
-3x -3y = 0
_____________________
-1x - 5y = -4

Answer Link
H1a2r3s4h5 H1a2r3s4h5
  • 02-03-2017
2x-2y=-4
Multiply eq.by 3
6x-6y=-12
-3x-3y=0
Multiply eq.by 2
-6x-6y=0
from both new eq.
6x-6y=-12
-6x-6y=0
So adding both eq. We get
-12y=-12
So y=1
From eq.1
2x-2y=-4
2x-2(1)=-4
2x-2=-4
2x=-4+2
2x=-2
x=-1
so x=-1 and y=1
Answer Link

Otras preguntas

one major goal of the congress of vienna was to
ANSWER FOR BRAINLIEST! 40 points! PLEASE HELP I DONT WANT TO FAIL MATH.
What is the most appropriate unit to describe the time you can drive a car based on the amount of gas
Hailey spent $12 to buy $2 fish her cousin spent double the amount on fish each fish cost the same amount how many fish do hailey and her cousin have altogether
Six consecutive numbers starting from 33 are multiplied. Which of these digits will be in the ONES' place in the resulting number?
Please help fast‼️‼️
whats 600 x 109302 plz help
Hot coffee is stirred with a spoon, the spoon gets hot due to
Sam wants to be named the greatest home run hitter of his baseball league. In the past 5 seasons he has hit 24 , 20, 23, 20, and 21 home runs, respectively. To
Does anyone know how to do this? If so, can you explain it?